Assessing Individual Change Using Short Tests and Questionnaires. (May 2014) - Kruyen, Peter M.; Emons, Wilco H. M.; Sijtsma, Klaas
In clinical contexts, tests and questionnaires are used to assess change at the level of the individual client. The difference between an individual client's posttreatment and pretreatment scores is used to decide about the degree to which the client benefited from a treatment. Because administration time is limited, clinicians prefer using short tests consisting of, say, at the most 15 items. Simulation research showed that shorter tests produce a higher risk of drawing incorrect conclusions about change in individual clients. Based on the simulation results, the authors provide guidelines for the number of items minimally required to reliably assess individual change. Using item response theory, they also provide guidelines for the minimally required local test information for individual-change assessment.